Environmental education in Brazil: trends and gaps from 2015 to 2019 (Research, Society and Development, 2022)
Here we carried out a review of the open-access literature concerning Environmental Education in the prominent Brazilian journals from 2015 to 2019, aiming to provide trends in the field of Environmental Education Research in Brazil and highlighted well-studied areas and potential research gaps. We found a total of 695 articles from four scientific journals that met the selection criteria, and identified five key results: i) a predominance of qualitative research approach; ii) sex-biased authorship skewed towards women; iii) high educational attainment, led by authors with doctoral degrees; iv) a majority of authors affiliated to public institutions, and v) a predominance of authors from institutions at the southeast region of Brazil. Therefore, our results highlight that the major gaps to be filled in Environmental Education are the lack of quantitative studies, low scientific production by private universities, and centralization of production in the southeast and south regions.